Central and local controls of monocytopoiesis influence the outcome of Leishmania infection. (November 2021) - Raybarman, Chandan; Bhattacharjee, Surajit
Abstract: Leishmaniases represent a complex of tropical and subtropical diseases caused by an intracellular protozoon of the genus Leishmania . The principal cells controlling the interaction between the host and the parasite Leishmania are monocytes and macrophages, as these cells play a decisive role in establishing the pathogenesis or cure. These cells are involved in controlling the growth of Leishmania and in modulating the adaptive immune responses. The heterogeneity and extensive plasticity of monocytes allow these cells to adjust their functional phenotypes in response to the pathogen-directed immunological cues. In Leishmania -infected host, the rate of myelopoiesis is augmented by enhanced monocytic lineage commitment and proliferation of myeloid progenitor cells both in the BM and at the site of infection. These newly generated monocytes play as "safe haven" for the parasite and also as the antigen-presenting cells for T cells to cause deregulated cytokine production. This altered monocytopoiesis is characterized by tissue-specific immune responses, spatiotemporal dynamics of immunoregulation and functional heterogeneity. In the presence of Th1 cytokines, monocytes exhibit a pro-inflammatory phenotype that protects the host from Leishmania . By contrast, in an environment of Th2 cytokines, monocytes display anti-inflammatory phenotype with pro-parasitic functions. In this review, we summarize the involvement of cytokines in the regulation of monocytopoiesis and differentiation of macrophages during leishmanial infection. Understanding the role of cytokines in regulating interactions between Leishmania and the host monocytes is key to developing new therapeutic interventions against leishmaniases.